Unleashing the Power of Docker and Kubernetes for Databases - Balakrishna Boddu (North American Journal of Engineering Research, 2022)
Current database systems are more complex Nowadays and demanding efficient management and scalability. Docker andKubernetes, powerful tools for containerization and orchestration, offer a robust solution. This Paper will explore how Dockerand Kubernetes can revolutionize database deployment, management, and scaling. We will deep dive into key concepts, bestpractices, and real-world use cases to demonstrate the significant benefits of adopting these technologies. By the end, attendeeswill have a clear understanding of how to leverage Docker and Kubernetes to optimize their database infrastructure and achieveunparalleled performance, reliability, and flexibility